Behavioral Activation Treatment for Smoking (BATS) in smokers with depressive symptomatology. Issue 2 (15th August 2016) - MacPherson, Laura; Collado, Anahi; Lejuez, Carl W.; Brown, Richard A.; Tull, Matthew T.
Abstract : Purpose: Cigarette smoking remains the primary preventable cause of mortality and morbidity globally. The overarching goal of the paper is to disseminate the Behavioral Activation Treatment for Smoking (BATS), which integrates behavioral activation principles with standard treatment guidelines to assist individuals in achieving short- and long-term smoking cessation. Through a series of sequential steps, BATS guides individuals who wish to quit smoking to increase their engagement in healthy, pleasurable, and value-consistent activities. Design/methodology/approach: The document provides the BATS rationale and contains an abridged manual for use by clinicians and/or researchers in the context of clinical trials. Findings: BATS is accruing empirical evidence that suggests its ability to promote successful smoking cessation outcomes while decreasing any associated depressive symptoms. Findings: BATS is accruing empirical evidence that suggests its ability to promote successful smoking cessation outcomes while decreasing any associated depressive symptoms. Practical implications: A description of key components, forms, and strategies to address common treatment barriers are included. Originality/value: BATS's strong roots in learning theories and its idiographic nature allow for the intervention to be implemented flexibly across a wide range of settings and smoking populations. The treatment may also be combined seamlessly with pharmacotherapies. BATS targets both cigarette smoking and depressive symptoms, which constitute a significant barrier to cessation, through a common pathway: increasing rewarding activities. The treatment offers a parsimonious complement to standard smoking cessation treatments.